Acid-catalyzed hydrolysis of triacylglycerols obeys monoexponential kinetics - Vega Ríos, Aracelly (1992)
The acid-catalyzed hydrolyses of triacetyl-glycerol and of tributyryl-glycerol take place following a simple monoexponential kinetic scheme. The result can be interpreted as all three ester groups reacting with approximately the same specific rate. This observation reported in 1920 is unusual, because the intrinsic reactivities of primary and secondary esters are different, and because as far as the reaction proceeds, the remaining ester groups have neighboring hydroxyl groups, which undoubtly alter the reactivity of the reaction centers, relative to the situation in the initial reactant structure. The phenomenom can be explained by considering that local solvation effects due to neighboring hydrophylic groups remain unchanged as the transition-state complex is formed in all three stages of the reaction.